2021
DOI: 10.3390/ijms22041973
|View full text |Cite
|
Sign up to set email alerts
|

Abscopal Effect of Frozen Autograft Reconstruction Combined with an Immune Checkpoint Inhibitor Analyzed Using a Metastatic Bone Tumor Model

Abstract: We evaluated the abscopal effect of re-implantation of liquid nitrogen-treated tumor-bearing bone grafts and the synergistic effect of anti-PD-1 (programmed death-1) therapy using a bone metastasis model, created by injecting MMT-060562 cells into the bilateral tibiae of 6–8-week-old female C3H mice. After 2 weeks, the lateral tumors were treated by excision, cryotreatment using liquid nitrogen, excision with anti-PD-1 treatment, and cryotreatment with anti-PD-1 treatment. Anti-mouse PD-1 4H2 was injected on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The number of CD8+ T cells infiltrating the abscopal tumor and tumor‐specific IFN‐ γ ‐producing spleen cells increased in the liquid nitrogen‐treated group. [ 136 ] Liquid nitrogen‐based cryo‐shocking of tumor cells can also be used in combination with adjuvants, as vaccines against lung cancer. Tadao found that the injection of MS‐Ap‐PAMA adjuvant in combination with liquid‐nitrogen‐treated tumor tissue (derived from Lewis lung carcinoma cells) into C57BL/6 mice markedly inhibited in vivo tumor recurrence and the development of rechallenged tumor, compared to those with commercial alum adjuvant.…”
Section: Cancer Vaccines Based On Whole Tumor Cell (Without Destroyin...mentioning
confidence: 99%
“…The number of CD8+ T cells infiltrating the abscopal tumor and tumor‐specific IFN‐ γ ‐producing spleen cells increased in the liquid nitrogen‐treated group. [ 136 ] Liquid nitrogen‐based cryo‐shocking of tumor cells can also be used in combination with adjuvants, as vaccines against lung cancer. Tadao found that the injection of MS‐Ap‐PAMA adjuvant in combination with liquid‐nitrogen‐treated tumor tissue (derived from Lewis lung carcinoma cells) into C57BL/6 mice markedly inhibited in vivo tumor recurrence and the development of rechallenged tumor, compared to those with commercial alum adjuvant.…”
Section: Cancer Vaccines Based On Whole Tumor Cell (Without Destroyin...mentioning
confidence: 99%
“…Cryotherapy accomplishes this by activating DCs and by inducing cytokine secretion, which is critical in antigen presentation and the antitumor immune response, respectively [ 70 ]. Similarly, the abscopal effect on the abscopal tumor was observed when a liquid nitrogen‐treated tumor‐bearing bone graft was reimplanted into a bone metastasis‐induced female C3H model; however, this effect was synergistically enhanced when cryotherapy was used in combination with an immune checkpoint inhibitor (ICI) anti‐programmed death‐1 (PD1) therapy due to the induction of the T‐cell response against tumors, which was absent in mice having frozen‐autograft alone [ 71 ]. After 1 month of cryoablation treatment, the primary carcinoid tumor shrank by 90%, with no growth in the metastatic tumor [ 72 ].…”
Section: Different Cancer Therapies Eliciting the Abscopal Effect And...mentioning
confidence: 99%
“…Recently, this phenomenon was proposed as a cancer-specific immunoenhancing effect triggered by tumor cell death [ 8 ], and the abscopal effect has been reported in various local therapies, such as RT, embolization, radiofrequency ablation (RFA), and cryotherapy [ 9 , 10 , 11 , 12 ]. In particular, cryotherapy is an area of current interest to us, as previous studies have investigated the immune elevating effects associated with frozen autografts [ 13 ].…”
Section: Introductionmentioning
confidence: 99%